Advantages of a smaller bodymass in humans when distance-running in warm, humid conditions - Denis, S. C.; Noakes, T. D. (European Journal of Applied Physiology, 1999)
A lower metabolic heat production in lighter runners at any given speed may be one reason why smallness of stature is an asset in distance running.